SIFAT KIMIA AIR OBYEK WISATA ALAM GUNUNG RIAN DI KABUPATEN TANA TIDUNG, KALIMANTAN UTARA - Mohammad Irwan Kurniawan; Karyati Kasiman (ULIN: Jurnal Hutan Tropis, 2017)
The management of tourism sector needs to control environment quality, such as potency of water pollution. The objective of this study was to know the water chemical properties in ecotourism area of Rian Mountain, District of Tana Tidung, Province of North Kalimantan. The water samples were taken at two sampling points, such as waterfall of Rian Mountain and Rian River. The tested water chemical properties were pH, dissolved oxygen (DO), sulphate (SO4), nitrite (NO2-N), biological oxygen demand (BOD5), chemical oxygen demand (COD), iron (Fe), manganese (Mn), and lead (Pb). The result showed that the water chemical properties in two sampling points based on Regulation of East Kalimantan Governor No. 02/2011 about The Management of  Water Quality and Water Pollution Control are included to Class I that is can be used to raw water for drinking water, and/or for the other purposes that required similar water quality to that purpose. Beside for potencial ecotourism area, tourism object of Rian Muntain in Tana Tidung can be alternative of clean water source to be consumed safely by the people who live in the area, because until now they do not receive water pipe facilities of MunicipalWater Works (PDAM) yet.